БЎЛҒУСИ МЕНЕДЖЕРЛАР БОШҚАРУВ КЎНИКМАЛАРИ ШАКЛЛАНИШИНИНГ ПСИХОЛОГИК ОМИЛЛАРИ - Махмудов, А.М.; Ниязов, Ас.Т.; Ниязов, Аб.Т. (SCIENCE and SOCIETY, 2016)
The article deals with the analysis of skills and competencies, promoting the professional development of future managers. The author studies psychological factors influencing on the development of managerial skills.
Keywords: professional formation; management skills of managers; professional competence; importance of socio-psychological state of the individual